1969
DOI: 10.1097/00132586-196904000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alterations in the Arterial Carbon Dioxide Tension on the Blood Flow Through the Cerebral Cortex at Normal and Low Arterial Blood Pressures

Abstract: It is well known that the cerebral blood flow alters in response to changes in the arterial carbon dioxide tension. However, it is not yet clear whether there are upper and lower limits of Paco, beyond which the cerebral vessels do not react. In addition, there have been no reports on the response of cerebral blood flow to alterations in Paco, in hypotensive states.The recent development by Ingvar (1961, 1962) of a rapid, easily repeatable, and relatively untraumatic method of estimating the blood flow throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
153
0
2

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(174 citation statements)
references
References 4 publications
19
153
0
2
Order By: Relevance
“…This has been exactly ob served repeatedly by many investigators (lngvar and Lassen, 1962;Fieschi et aI. , 1965;Harper and , 1965;Lassen, 1965a;Jamieson and Halsey, 1973;Pasztor et aI., 1973;Meyer et aI., 1980) using krypton, xenon, or H2 as an indicator and was also confirmed by us in another series of experiments (von Kummer, 1984b).…”
Section: Washout Phasesupporting
confidence: 70%
“…This has been exactly ob served repeatedly by many investigators (lngvar and Lassen, 1962;Fieschi et aI. , 1965;Harper and , 1965;Lassen, 1965a;Jamieson and Halsey, 1973;Pasztor et aI., 1973;Meyer et aI., 1980) using krypton, xenon, or H2 as an indicator and was also confirmed by us in another series of experiments (von Kummer, 1984b).…”
Section: Washout Phasesupporting
confidence: 70%
“…11,12 Although resting CBF may be preserved after SCI, cerebrovascular reserve (i.e., the ability of the cerebrovascular system to respond to acute increases in metabolic demand, mechanical or neural stimuli) may be affected, resulting in an insufficient CBF response. 13 Supporting this contention, elegant work by Harper and Glass 14 showed that progressive hypotension abolishes the capacity of the cerebrovasculature to dilate or constrict.…”
Section: Introductionmentioning
confidence: 99%
“…18 As cerebral perfusion pressure is a critical component of CBF control, it is possible that NVC mediates the relationship between reduced BP and cognitive function in SCI. 14 Wecht et al 19 partially examined this relationship by showing the MCA flow velocity response to cognition (i.e., Stroop test) was not different between AB and SCI. Although the internal carotid/MCA provides 475% of total CBF, arteries responsible for perfusing the brainstem (i.e., vertebral/posterior cerebral arteries (PCA)) have been shown to be more responsive to various cognitive stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…In using a P aco2 change to produce changes in CBF, it seemed reasonable to choose values at the ex tremes of variations that might occur under physi ological stress and not to employ extremes which result in indeterminate secondary effects or are be yond those attainable by a physiological situation. For Paco2, this range probably extends from 15-30 mm Hg to 60-70 mm Hg (Reivich, 1964;Harper and Glass, 1965;James et aI., 1969;Sage et aI., 1981). This range includes the straight-line portion of the curves published by many investigators for CBF versus Paco2 in a variety of animals.…”
Section: The Methods For Cbf Measurementmentioning
confidence: 99%